Pengaruh Struktur Modal, Struktur Aktiva Dengan Variabel Intervening Kinerja Keuangan dan Manajemen Laba Terhadap Intensitas Pajak Efektif Pada Perusahaan Subsektor Industri Rokok yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2022 - Primardiningtyas, Filzah; Hwihanus, Hwihanus (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2023)
The study aims to analyze the impact of the capital structure, asset structure on effective tax rates with intervening variables of financial performance and profit management on the BEI-listed tobacco industry in 2019-2022. The study uses descriptive quantitative data with secondary data obtained from the annual report of the cigarette company for 2019-2022. The population of this study is cigarette companies that are listed in the BEI 2019-2022 using purposive sampling method. The research technique uses Smart-PLS4 software with SEM- PLS analysis consisting of an external model and an inner model. The test results showed from the nine hypotheses, that only the capital structure against profit management and the asset structure towards profit management were significant with a negative influence.